Catheter-associated urinary tract infection reduction in critical care units: a bundled care model. Issue 4 (23rd December 2021) - Van Decker, Stephanie Grana; Bosch, Nicholas; Murphy, Jaime
Abstract : Catheter-associated urinary tract infections (CAUTIs) represent approximately 9% of all hospital acquired infections, and approximately 65%–70% of CAUTIs are believed to be preventable. In the spring of 2013, Boston Medical Center (BMC) began an initiative to decrease CAUTI rates within its intensive care units (ICUs). A CAUTI taskforce convened and reviewed process maps and gap analyses. Based on Centers for Disease Control and Prevention (CDC) and Institute for Healthcare Improvement (IHI) guidelines, and delineated by the Healthcare Infection Control Practices Advisory Committee 2009 guidelines, all BMC ICUs sequentially implemented plan–do–study–act cycles based on which measures were most easily adaptable and believed to have the highest impact on CAUTI rates. Implementation of five care bundles spanned 5 years and included (1) processes for insertion and maintenance of foley catheters; (2) indications for indwelling foley catheters; (3) appropriate testing for CAUTIs; (4) alternatives to indwelling devices; and (5) sterilisation techniques. Daily rounds by unit nursing supervisors and inclusion of foley catheter necessity on daily ICU checklists held staff accountable on a daily basis. With these interventions, the total number of CAUTIs at BMC decreased from 53 in 2013 to 9 in 2017 (83% reduction) with a 33.8% reduction in indwelling foley catheter utilisation during the same time period. Adapted protocols showed success in decreasing the CAUTI rate and indwelling foley catheter usage in all of the BMC ICU's. While all interventions had favourable and additive trends towards decreasing the CAUTI rate, the CAUTI awareness education, insertion and removal protocols and implementation of PureWick female incontinence devices had clear and significant effects on decreasing CAUTI rates. Our project provides a framework for improving HAIs using rapid cycle testing and U-chart data monitoring. Targeted education efforts and standardised checklists and protocols adapted sequentially are low-cost and high yield efforts that may decrease CAUTIs in ICU settings.